Analysis and research on the integration of education, technology and industry in smart education - Shao Haiyan; Lv Jie; Sun Xuan; Wang Na; Wang Peng; Zhu Dongqing; Xue Hao; Chen Bin; Ma Yuzhen (ITM Web of Conferences)
Under the wave of digitalization and intelligence, smart education is becoming an important force to promote educational modernization, promote educational equity and improve educational quality. This manuscript elucidates the principle, features, and current progress of intelligent learning, with a particular emphasis on the examination of digital education strategies from different nations. From multiple dimensions, the differences between traditional education and smart education are compared and analyzed. The analysis examines the specific progression of intelligent education across different nations, emphasizing the fusion of educational and technological fields, the convergence between education and the industrial sector, and the tripartite integration of industry, academia, and research, along with the challenges. The focus of this manuscript is on pioneering integration strategies through case-based teaching, the joint educational framework of industry-academic convergence, the development of a multifaceted assessment approach, and the new ‘teacher-machine-student’ teaching model. The manuscript also discusses the future development trend of smart education. Research shows that the deep integration of smart education requires multi-party collaboration, continuous innovation of teaching models, further improvement of the evaluation system, and the fostering of creative individuals equipped for the demands of forthcoming societal challenges.